Armstrong, Nigel, y Federico M. Federici, eds., Translating Voices, Translating Regions, Roma, Aracne, 241p. - Orozco, Wilson (Íkala, Revista de Lenguaje y Cultura, 2006)
Armstrong, Nigel, y Federico M. Federici, eds., Translating Voices, Translating Regions, Roma, Aracne, 241p.